VIRTUAL BOOK EXHIBITION AS A MODERN FORM OF LIBRARY SERVICE (FROM EXPERIENCE OF KRYVYI RIH STATE PEDAGOGICAL UNIVERSITY LIBRARY) - Shestopalova, Oksana V. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2019)
The article discusses virtual exhibitions as one of the innovative forms of library work; defines modern methods of their creation, approaches to organizing them and their place in the system of electronic information resources. The article dwells upon the ways of implementing innovations into the creation of library exhibitions.